Lack of Judges, Lack of Justice? : Evidence from Vacancies at the Czech Constitutional Court - Žáček, Ondřej (2017)
This thesis deals with the question whether judges at the Constitutional Court of the Czech Republic respond to the increase in average caseload through the change of their decision-making. My model of binding time constraint that restricts judges (and the Constitutional Court) in their output optimization predicts that vacancies along with the Court’s growing workload should rationally lead to more frequent procedural rejections of the constitutional complaints and to the protraction of the length of proceedings. Subsequent empirical tests of dataset that consists of several tens of thousands of cases resolved by the Constitutional Court between 2002 and 2015 tend to only confirm the second aforementioned hypothesis.